Sebaran Dan Nilai Indeks Jasa Ekosistem Pengaturan Kualitas Udara, Iklim Dan Air Di Kabupaten Konawe - La Baco Baco Sudia (Universitas Halu Oleo, 2021)
Ecosystem services to regulate air quality, climate, water system and water purification are important ecosystem services for human life and other living things. The objective of the research was to analyze the distribution and value of ecosystem services index of air quality, climate, water system and water purification of Konawe Regency. This research was conducted through the study of ecoregion characteristics, covering landforms, natural vegetation types and land cover. Data analysis includes the calculation of ecosystem services index and spatial distribution of ecosystem services index. The results showed that the dominant type of landform in Konawe Regency was the structural hills of metamorphic rock material with natural vegetation in the form of forests and the dominant land cover was primary dry land forests.The average value of the Ecosystem Services Index (ESI) of air quality regulation were 2.88 (medium), climate regulation and water system arrangements were 3.18 (medium) and 3.12 (medium) and water purification settings was 2.12 (low). The average value of the ecosystem services index of the four types of regulatory services was 2.83 with a moderate category. The average ESI value of Sub District of Latoma, Asinua, Routa, Abuki and Meluhu were 3.92, 3.65, 3.62, 3.51 and 3.49 with high categories, respectively. The performance of environmental services of air quality regulation is dominated by a high category of 221,489.56 hectares or 41.99 percent, while climate regulation was dominated by a very high category of 243,516.50 hectares or 46.17 percent. The performance of ecosystem services of water system and water purification arrangements reached an area of 235,459.44 hectares or 44.64 percent and 32,723.16 hectares or 43.04 percent respectively.Keywords: ecoregion, ecosystem services index, regulating ecosystem services,spatial distributionJasa ekosistem pengaturan kualitas udara, iklim, tata air dan pemurnian air merupakan jasa ekosistem penting terhadap kehidupan manusia dan mahluk hidup lain. Penelitian ini bertujuan untuk menganalisis sebaran dan nilai indeks jasa ekosistem pengaturan kualitas udara, iklim, tata air dan pemurnian air Kabupaten Konawe. Penelitian ini dilakukan melalui kajian karakteristik ekoregion, mencakup bentang lahan, tipe vegetasi alami dan tutupan lahan. Analisis data meliputi perhitunganindeksjasaekosistem dan sebaranspasialindeksjasaekosistem. Hasil penelitian menunjukkan bahwa tipe bentang lahan yang dominan di Kabupaten Konawe adalah perbukitan structural lipatan bermaterial batuan metamorfik dengan vegetasi alami berupa hutanpamah (non dipterokarpa) dan tutupan lahan dominan adalah hutan lahan kering primer. Rata-rata nilai Indeks Jasa Ekosistem pengaturan kualitas udara adalah 2,88 (sedang), pengaturan iklim dan pengaturan tata air masing-masing sebesar 3,18 (sedang) dan 3,12 (sedang) dan pengaturan pemurnian air adalah 2,12 (rendah). Nilai rata-rata indeks jasa ekosistem dari empat jenis jasa pengaturan tersebut adalah 2,83 dengan kategori sedang. Nilai IJE rata-rata Kecamatan Latoma yakni 3,92, Kecamatan Asinua sebesar 3,65, KecamatanRouta sebesar 3,62, serta KecamatanAbuki dan KecamatanMeluhu masing-masing 3,51 dan 3,49 dengan kategori tinggi. Kinerja jasa lingkungan pengaturan kualitas udara didominasi oleh kategori tinggi seluas 221.489,56 hektaratau 41,99%, sementara itu pengaturan iklim didominasi oleh kategori sangat tinggiseluas 243.516,50 hektaratau 46,17%. Kinerja jasa ekosistem pengaturan tata air dan pengaturan pemurnian air mencapai luas masing-masing 235.459,44 hektaratau 44,64% dan 32.723,16 hektaratau 43,04%.Kata Kunci:ekoregion, jasa ekosistem pengaturan, indeks jasa ekosistem, sebaran spasial